2009
DOI: 10.1890/08-0344.1
|View full text |Cite
|
Sign up to set email alerts
|

A single phosphorus treatment doubles growth of cyanobacterial lichen transplants

Abstract: Lichens are reputedly slow growing and become unhealthy or die in response to supplements of the usual limiting resources, such as water and nitrogen. We found, however, that the tripartite cyanobacterial lichen Lobaria pulmonaria doubled in annual biomass growth after a single 20-minute immersion in a phosphorus solution (K2HPO4), as compared to controls receiving no supplemental phosphorus. This stimulation of cyanolichens by phosphorus has direct relevance to community and population ecology of lichens, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 29 publications
4
38
4
Order By: Relevance
“…The lack of a strong growth response for fertilized Lobaria in our experiment at Tenmile contrasts with the doubling of Lobaria growth rates with P fertilization observed previously at the Wren site by McCune and Caldwell (2009), using the same P-treatment concentrations, on the same species, in the same climate regime. Although the favorable weather and consistently high growth rates we observed at Tenmile should correspond with high P-demand, P did not limit Lobaria growth in the current experiment.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The lack of a strong growth response for fertilized Lobaria in our experiment at Tenmile contrasts with the doubling of Lobaria growth rates with P fertilization observed previously at the Wren site by McCune and Caldwell (2009), using the same P-treatment concentrations, on the same species, in the same climate regime. Although the favorable weather and consistently high growth rates we observed at Tenmile should correspond with high P-demand, P did not limit Lobaria growth in the current experiment.…”
Section: Discussioncontrasting
confidence: 99%
“…Because growth rates depended on initial mass for both species, we removed the effects of initial mass prior to testing for differences among treatments. Combining data from all treatments, growth rate (G) had a strong negative exponential relationship to initial mass (M 0 ), a trend not seen by McCune and Caldwell (2009). Thus, in the current study, thalli that were smaller prior to transplanting grew faster than thalli that were initially larger.…”
Section: Resultsmentioning
confidence: 48%
See 1 more Smart Citation
“…Coxson and Coyle (2003) supported this hypothesis and predicted higher photosynthetic rates for Alectoria sarmentosa in the lower canopy where it occurs, but concluded that growth responses alone did not explain the niche partitioning in pendulous lichens. Recently, phosphorus availability (McCune and Caldwell 2009) and exogenous carbohydrates (Campbell et al 2013) containing contrasting pigments are taxonomically more related to each other than to the genera (Alectoria and Usnea) containing usnic acid (Thell and Moberg 2011). Both melanins (e.g., Gauslaa and Solhaug 2001) and usnic acid (McEvoy et al 2007) screen light, and thus protect underlying photobionts.…”
Section: Introductionmentioning
confidence: 99%
“…Tree species-specific levels of canopy leaching is a likely explanation also for the elevated contents of P in lichens in the dripzone of beech trees. Because lichen growth can be P-limited in oligotrophic forests (Benner et al 2007;Johansson et al 2011;McCune and Caldwell 2009), the higher contents of the macronutrients P and K in lichen transplants on beech would likely influence the epiphytic community. Cyano-and cephalolichens, having a capacity to fix N, need relatively high bark pH (Gauslaa 1985;Gauslaa and Holien 1998), and seem to be favored by elevated P (Benner 2011), meaning that canopy throughfall rich in base cations and P can cause cascading effects through increased N-fertilization of natural forest ecosystems.…”
Section: Discussionmentioning
confidence: 99%